Leptin Does Not Influence TSH Levels in Obese Short Children - Adamczewska, Katarzyna; Adamczewski, Zbigniew; Lewiński, Andrzej; Stawerska, Renata (Frontiers in Endocrinology, 2022)
Introduction: Growth hormone (GH) and thyroid hormones are important for children growing. In some obese children a slightly elevated TSH concentration is observed. This observation may be adaptive mechanism in response to elevated leptin, i.e. the hormone which formation of pro-TRH in the hypothalamus. The increased TSH may reflect also the necessity of maintaining of resting energy expenditure or may be a result inappropriate low FT4 concentration. Thus, we evaluated serum TSH and FT4 concentrations in idiopathic short stature (ISS) children (non GH-deficient), depending on their nutritional state and selected adipocytokines levels. Methods: The study group included 115 children (50 girls and 65 boys) with ISS, aged (mean±SD) 10.4±3.34 years. In each child, lipids, TSH, FT4, IGF-1, maxGH during the stimulation tests, leptin, adiponectin and resistin concentrations were determined. Based on BMI SDS, 3 subgroups: slim (n=26), obese (n=21) and normal weight (n=68) were distinguished. Results: The levels of leptin, total cholesterol and LDL-cholesterol in obese short children were significantly higher than in children from other subgroups. In turn, the levels of adiponectin, resistin, TSH and FT4 did not differ between subgroups. In 7% children, a slightly elevated TSH level was found, with a similar frequency in subgroups. There was no correlation between leptin and TSH or FT4 levels. The higher the leptin, the lower maxGH in clonidine stimulation test was recorded. Conclusions: It seems that in obese children with idiopathic short stature (non GH-deficient children) leptin does not increase TSH secretion (e.g. due to hypothalamic regulatory disturbances). It is probable that this may be a cause of relative hypothyroxinemia, which is responsible for decrease height velocity and worse cholesterol profile in those children.